The Implementation of Canva-Assisted Team Games Tournament Model to Improve Students’ Mathematics Learning Outcomes - Dani, Sesliyanti; Abdullah, Abdul Wahab; Irfah, Auli (IKIP Siliwangi, 2026)
This study aims to improve students' mathematics learning outcomes on sequences and series material through the Teams Games Tournament (TGT) cooperative model assisted by Canva. The research involved 21 students from class X-A at SMA Negeri 1 Pinolosian during the 2024-2025 academic year. Using Classroom Action Research (CAR) conducted in two cycles, each stage included planning, acting, observing, and reflecting. The results showed significant improvements in both process and output. Teacher activity progressed from 'Fair' (C) in Cycle I to 'Good' (B) or 'Excellent' (SB) in Cycle II. Similarly, student activity improved from the 'Fair' category to 'Excellent' as enthusiasm and collaboration increased through Canva’s visual media and healthy competition. Most notably, students' classical mastery jumped from only 43% in Cycle I to 90% in Cycle II, successfully surpassing the 80% success indicator. The integration of Canva helped visualize abstract concepts, while the TGT tournament element effectively boosted student motivation and teamwork. It can be concluded that the TGT model assisted by Canva is an effective strategy to enhance mathematics learning outcomes for tenth-grade students.